Trade and Industrial Policy Under Oligopoly: Comment - Csaplar, Wilfrid W.; Tower, Edward (Quarterly Journal of Economics, 1988)
Wilfrid W. Csaplar, Jr., Edward Tower; Trade and Industrial Policy Under Oligopoly: Comment, The Quarterly Journal of Economics, Volume 103, Issue 3, 1 August 1